2008
DOI: 10.1080/02652030701713939
|View full text |Cite
|
Sign up to set email alerts
|

Pilot survey of aflatoxin–albumin adducts in sera from Egypt

Abstract: Aflatoxins are potent liver carcinogens that frequently contaminate cereals in developing countries. Aflatoxin exposure has been predicted in Egypt but, to date, no studies have measured the level of aflatoxin-albumin (AF-alb) adducts as a validated biomarker to assess exposure. In this pilot survey, a limited number of sera samples, available from a hepatocellular carcinoma (HCC) case-control study in Egypt, were analysed. AF-alb was detected in 24/24 samples from HCC-negative individuals (geometric mean 9.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…In middle-income countries or regions where exposures may be more moderate, probiotic interventions have been suggested (177) ; these probiotics restrict aflatoxin bioavailability by binding and then shuttling the toxin through the gastrointestinal tract. Such an approach has been suggested as plausible in a region such as Egypt (178) where sources of exposure are less well defined (26,27,60) . In terms of growth, this approach was successful in a rodent model in that in the intervention arm, both the aflatoxin-driven growth faltering was improved and the aflatoxin biomarker level was reduced (179) .…”
Section: Discussionmentioning
confidence: 99%
“…In middle-income countries or regions where exposures may be more moderate, probiotic interventions have been suggested (177) ; these probiotics restrict aflatoxin bioavailability by binding and then shuttling the toxin through the gastrointestinal tract. Such an approach has been suggested as plausible in a region such as Egypt (178) where sources of exposure are less well defined (26,27,60) . In terms of growth, this approach was successful in a rodent model in that in the intervention arm, both the aflatoxin-driven growth faltering was improved and the aflatoxin biomarker level was reduced (179) .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies of human populations exposed to diets naturally contaminated with AFs revealed positive correlations between the high incidence of liver cancer in Africa and elsewhere and dietary intake consumption of AF [54]. AF consumption raises the risk of liver cancer by more than ten-fold compared to either exposure alone in people with hepatitis B and C viral infection [72]. …”
Section: Public Health Importance Of Mycotoxins In African Countriesmentioning
confidence: 99%
“…In Ghana, higher levels of AFB1-alb adducts in plasma were associated with lower percentages of certain leukocyte immunophenotypes [42] (Table 2); in addition, a close association between anemia in pregnancy and AFs among pregnant women in Kumasi was reported [69]. Similarly, a study in Gambian children found an association between serum AFs-alb levels and reduced salivatory secretory IgA levels [72] (Table 2). Additionally, AFs and hepatitis B virus exposure appeared to interact synergistically to substantially increase the risk of cirrhosis in Gambia [49] (Table 2).…”
Section: Public Health Importance Of Mycotoxins In African Countriesmentioning
confidence: 99%
“…Exposures in regions such as Egypt and Brazil are perhaps intermediate in exposure [64, 65, 74, 99, 112] but these exposures are still of concern. A number of approaches have been used to assess the concentration of aflatoxin exposure biomarkers including ELISA, RIA, HPLC with fluorescence (HPLC-Fl) detection, LC-MS and LC-MS/MS, and AMS; each approach has advantages and disadvantages, though readers should rather be aware that it is not always possible to compare data directly from one approach to another.…”
Section: Mycotoxin Exposure Biomarkersmentioning
confidence: 99%